EFFECT OF CASH HOLDING ON FIRM VALUE WITH OWNERSHIP STRUCTURE AS A MODERATING VARIABLE IN INDONESIA COMPANY - Sumiati, Sumiati (Universitas Brawijaya, Indonesia, 2020)
The purpose of this study is to investigate the relationship between cash holdings and firm value in non-financial companies in Indonesia. This study places managerial ownership as a moderating factor for cash holding and firm value. The results show that cash holding has an effect on firm value and managerial ownership is able to moderate the relationship between cash holding and firmvalue. Moderation test results show that of the managerial ownership variable can moderate the relationship of cash holding and firm value, but this moderation relationship weakens where the greater the managerial ownership is, the weaker the relationship of cash holding to the value of the company. These results indicate that managerial ownership that is too large is feared to result in not being able to optimize the company's cash management which then results in a decline in the value of the company.